In vitro maturation of Southern white rhino (Ceratotherium simum simum) oocytes - Webb, E.C. (Edward Cottington) (University of Pretoria, 2024)
Dissertation (MSc Agric (Animal Science) Production Physiology and Product Quality)--University of Pretoria, 2024.